Inside Front Cover: Strategies for visualizing inflammation (View 1/2021). Issue 1 (6th February 2021) - Zhang, Xinping; Liu, Xiaoyang; Guo, Yuxin; Wu, Fu‐Gen
Abstract : In article number 20200025, Fu‐Gen Wu and co‐workers describe the probes and techniques that can realize inflammation visualization. Specifically, the review focuses on some probes that can target or visualize the inflammatory sites by specific binding to inflammation‐related molecules (active targeting), being internalized by inflammatory cells (immunocyte‐mediated targeting), or becoming detectable only under inflammatory conditions (responsive targeting). This review also discusses the use of various techniques like optical imaging (e.g., fluorescence imaging, bioluminescence imaging, and chemiluminescence imaging), positron emission tomography, single photon emission computed tomography, computed tomography, magnetic resonance imaging, ultrasound imaging, and photoacoustic imaging for inflammation visualization.